Knowledge and Practice of Road Safety Rules and Regulations among Secondary School Students (Prithvi Academic Journal, 2018)
Road traffic accidents are increasing in alarming ways. During adolescence period driving for curiosity, careless driving, and peer pressure are most common resulting high road traffic accidents. The main objective of the study was to explore the knowledge and practice of road safety rules and regulations. A descriptive cross sectional study design was used to conduct the study. Non-probability quota sampling technique was used to select 240 respondents from 800 students of class 11 and 12 from Pokhara Secondary School. Self-administered questionnaire was used to collect the information from respondents. The obtained data was entered on SPSS 16 version program and analyzed and interpreted by using descriptive statistics and inferential statistics. The findings revealed that more than half (59.2%) of the respondents had moderately adequate knowledge. Nearly three-forth (70.4%) of the respondents had average practice as a pedestrian and 75.7 percent of the respondents as a driver had average practice. Only 7.5 percent of the respondents were exposed to road traffic accident and high speed was the main cause of accident. More than three quarter (75.7%) had always driven vehicles without license. There was significant association (p=0.034) between the faculty of respondents (science and management) and level of knowledge of respondents on road safety rules and regulations. The study concluded that there was moderate level of knowledge and average level of practice of both drivers and pedestrians on road safety rules and regulations among secondary school students. It therefore suggests awareness programs on road safety rules and regulations are significant or school students to promote safety.